Stability Calculation of Irregular Structures with Irregular Disorder During Seismic Impact - Zaza Jangidze (AGG+)
From the point of view of modern construction, the damage to reinforced concrete large-panel and frame buildings is especially interesting. The construction of this building is very diverse. Their use has a short history. Therefore, the systematisation of damages and generalisation of results for such buildings is more difficult. Below are some statements sufficiently substantiated with factual material. It is similar to the skeleton of large-panel buildings. However, the resistance of reinforced concrete wall panels is, of course, much higher than the resistance of stone piles. That is why the panels themselves are rarely damaged by earthquakes. Relatively weak points of large-panel buildings are the edges of the panels, the support nodes on the roof panels and other connections. It is in these places that cracks, broken corners and other injuries develop during earthquakes. Three methods of restoration-reconstruction of damaged large-block multi-story buildings are proposed: metal diagonal web member and system-variable rigid in the interior space of the building, using today's terminology with seismic insulators, with the arrangement of additional frames; with reinforced-concrete pylons built over the entire height and perimeter of the building and by arranging loggias in their space; By building pylons along the longitudinal facades of the building and building a floor/floors on top of the building, along with arranging additional frames with seismic insulators if necessary.